How bank capital structure decision-making change in recessions: Covid-19 evidence from Pakistan - Khalil Ullah Mohammad (Asian Journal of Economics and Banking (AJEB), 2022)
Purpose - This study contributes to existing literature by investigating bank capital structure dynamics during the Covid-19 pandemic. The role of contemporary bank-specific determinants of capital structure during this period is analyzed. Design/methodology/approach - An independent t-test is carried out to check the response of bank leverage to the crisis. Using fixed effect estimation and difference general method of moments (GMM), the impact of the shock is examined. An unbalanced quarterly data set from 2016q1 to 2020q3 of all commercial banks in Pakistan is used. Findings - The study finds that due to procyclicality of capital, during the Covid-19 crisis, the banks preempted a fall in capital and improved their capital positions. The role of bank specific variables in determining capital structure like profitability, size and competition weakened during this period. Evidence suggests that policy rate intervention by the central bank was a significant factor in capital structure decisions during the Covid-19 period. The study finds that macroeconomic shocks have significant impact on capital structure decision-making of banks which goes beyond the bank-specific factors. Originality/value - It finds evidence of a moderating role of monetary policy in capital structure decision-making which has not been previously highlighted in literature. Monetary policy is found to become an important factor deciding the capital structure of banks during the Covid-19 first 3 quarters. This study also explores the impact of Covid-19 on the bank-specific determinants of capital structure of banks.
Keywords: G10; G21; G32; 330; Capital structure; Central banking; Covid-19; Financial crisis; Leverage